A "Testimonie"'s stance: Editorial positioning in Ælfric’s "Sermo in Die Pascae" - Mele-Marrero, Margarita (Adam Mickiewicz University, 2012)
Being one of the first texts to reproduce in printed form the Anglo-Saxon characters, A Testimonie of Antiquity, basically an edition of Ælfric’s “Sermo in Die Pascae”, has been the object of philological studies. Its subject matter related to the Anglican reform has also been analysed from a religious perspective. This article intends to focus on a different aspect, the reason for the text’s success evidenced in its several reproductions and content discussions, which have reached the 20th century. We claim the main credit for this success is to be given to its editors and, therefore, a pragmatic analysis concentrating on stance and engagement (Hyland 2005, 2009) is an adequate study frame. The conclusions will reveal how although there are quantifiable markers that facilitated the positive reception of the text, there were other elements (closer to modern writing implements) the authors utilized to achieve their final objective.